Knowledge and attitude on HIV/AIDS in a fishing community - Samsuddin, Niza; Ab Rahman, Jamalludin; Akter, Seikh Farid Uddin; Alwi, Mariah (Japan International Cultural Exchange Foundation (JICEF), 2010)
Objective: The purpose of the research is to have a better understanding on perception, knowledge and attitude towards HIV/AIDS in a fishermen's village of East Coast, Malaysia. The findings will be used to further improve HIV/AIDS intervention programmes. Design: A cross sectional study was conducted among adult Malays aged 18 to 49 in a fishermen's community of East Coast, Malaysia. Material and Methods: The research employed systematic random sampling from the sampling frame of houses. The data was collected through face-to-face interviewed questionnaire. Knowledge and attitude questions were scored and presented as percentage. Data was analyzed using SPSS 15. Results: The study involved 340 respondents, 61.5%(209) females and 38.5%(131) males. About 77.3%(262) of respondents admitted that HIV/AIDS was a serious problem in their village. Among these respondents, 96.9%(257) had the perception that it was due to intravenous drug user and 18.2%(48) believed it was due to free sex practice. The age group of 29-38 and respondents who had experience with HIV/AIDS personally, had significantly higher percentage knowledge score compared to other age groups and groups of respondent who had no experience. Fishermen showed significantly lower percentage knowledge score compared to other occupation groups. Respondents under poverty level were significantly associated with lower percentage of knowledge and attitude scores. In general, individual analyses of knowledge and attitude questions revealed that there were still high percentages of incorrect and unsure answers. Conclusion: Intravenous drug users and free sex practice are the predominant believed risk behavior by the community. The younger population and fishermen are the prime populations to whom education on HIV/AIDS should be given. Future study should explore the pattern of HIV/AIDS risk factors in the community for better intervention programme.